Observations of transverse Z mode and parametric decay in the solar wind. Issue 8 (26th August 2013) - Kellogg, P. J.; Goetz, K.; Monson, S. J.; Opitz, A.
Abstract: [1] The frequency resolution of the Time Domain Samplers of the S/WAVES experiments on the STEREO spacecraft has allowed clear observations of the nature of the Langmuir‐Z‐mode waves observed in the solar Wind in conjunction with Type III radio bursts. These include observations of transverse polarization of what are usually identified as Langmuir waves, observations of three‐wave decay, indications of the cause of the broadening of the spectrum of the observed waves, new understanding of the threshold for the three‐wave‐decay instability, and contributions to the understanding of conversion of these waves to electromagnetic waves. Analysis, using the decay relations, shows that decay often occurs to the Z mode, or near it. Z‐mode waves cannot be produced directly by the electrons of Type III bursts. The damping of Z mode and near Z mode is very small, accounting for the common occurrence of this nonlinear process. In particular, three‐wave parametric decay of a Langmuir wave to another Langmuir wave has become recognized as the dominant nonlinear process for Langmuir waves from Type III bursts. It is found, however, that decay usually leaves much of the wave energy in the daughter wave and that this wave often falls in a region where modulational instability must be considered in addition to three‐wave decay. On rare occasions, further decays follow the first. In these cases, the path length of the stimulating electron beam can sometimes be determined. Key Points: Three wave decay is common in solar wind Common because the daughter is fast or relativistic and has low damping Primary waves are in Zakharov region 1. the daughter may not be